Influence of coconut fibres and lime on the properties of soil-cement mortar - Humphrey Danso (Case Studies in Construction Materials, 2020)
Stabilisation of earth-based materials continues to gain attention among researchers in the field of construction. This study investigates the influence of coconut fibres and lime on the properties of soil-cement mortar. Fibres of 0.2–0.8 %; the lime of 0–15 %; cement of 5 % by weight of soil were used and tested for density, water absorption, compressive strength, tensile strength and SEM/EDS. There were improved density, water-resistance and erosion of the specimen. The optimum strength was recorded at 0.2 % fibre and 5 % lime addition of the specimen. The study concludes that coconut fibres and lime positively influences soil-cement mortar properties for construction application.